Ricardo Silva Romero, Río Muerto. Bogotá: Alfaguara. Penguin Random House. 2020, 156 pages. - López-González, Rosendo; Ramírez-Valencia, Astrid (Visión electrónica, 2021)
Ricardo Silva Romero, Río Muerto